2001
DOI: 10.1016/s0370-2693(00)01352-6
|View full text |Cite
|
Sign up to set email alerts
|

Casimir effect on the radius stabilization of the noncommutative torus

Abstract: We evaluate the one-loop correction to the spectrum of Kaluza-Klein system for the φ

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…In this letter, we are interested in studying the Casimir effect in the presence of extra compactified dimensions. The research on Casimir effect in the scenarios with extra dimensions have been studied in the context of string theory [26,27,28,29], dark energy and cosmological constant [16,17,18,19,21,22,25,30,31,32,33,34,35,36,37], as well as stabilization of extra dimensions [23,24,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. Casimir force for massless scalar field with Dirichlet boundary conditions on a pair of parallel plates inside space with extra dimensions compactified to a torus T n = (S 1 ) n have been calculated in [54,55,56,57,58,59].…”
mentioning
confidence: 99%
“…In this letter, we are interested in studying the Casimir effect in the presence of extra compactified dimensions. The research on Casimir effect in the scenarios with extra dimensions have been studied in the context of string theory [26,27,28,29], dark energy and cosmological constant [16,17,18,19,21,22,25,30,31,32,33,34,35,36,37], as well as stabilization of extra dimensions [23,24,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. Casimir force for massless scalar field with Dirichlet boundary conditions on a pair of parallel plates inside space with extra dimensions compactified to a torus T n = (S 1 ) n have been calculated in [54,55,56,57,58,59].…”
mentioning
confidence: 99%
“…• The question how vacuum fluctuations affect the * Electronic address: katjap@th.physik.uni-frankfurt.de stability of extra dimensions has been explored in [16,17,18,19,20,21]. Especially the detailed studies in the Randall-Sundrum model have shown the major contribution of the Casimir effect to stabilise the radion [22,23,24,25].…”
mentioning
confidence: 99%
“…On the one hand, it has been investigated as a candidate for the dark energy that accounts for the accelerated expansion of the Universe [3][4][5][6][7][8][9]. On the other hand, it was studied for its role in the stabilization mechanism of extra dimensions [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%